A DNAzyme-mediated signal amplification biosensor for ultrasensitive detection of lead ions based on SERS tags. Issue 1 (27th October 2022) - Teng, Wanqing; Zhao, Jing; Li, Qi; Shi, Pengfei; Zhang, Jing; Yan, Mei; Zhang, Shusheng
Abstract : A trace lead ion (Pb 2+ ) detection platform combining surface-enhanced Raman spectroscopy (SERS) with nucleic acid cycle multiple signal amplification. Abstract : The accumulation of trace heavy metals in the human body can be extremely damaging. Especially in the rapidly developing modern industrial society, heavy metal pollutants in the water environment are becoming more and more serious. Therefore, it is urgent to establish a rapid, accurate, effective and low-cost method for the detection of trace heavy metals. In this work, we propose a trace lead ion (Pb 2+ ) detection strategy combining surface-enhanced Raman spectroscopy (SERS) with nucleic acid rolling circle amplification (RCA) for multiple signal amplification. Lead ions can specifically bind with Pb 2+ -dependent DNAzyme to achieve efficient cleavage of the substrate. Then, trace Pb 2+ can be ultrasensitively detected by RCA and SERS based on biological barcoding techniques. Finally, we obtained a limit of detection (LOD, at a signal-to-noise ratio 3) of 3.1 × 10 −17 M for Pb 2+ and a linear relationship in the range of 10 −16 –2 × 10 −12 M. Additionally, the results of the interferometric test showed that the method is not affected by other metal ions and has good selectivity. Meanwhile, the formula provides a new and effective idea for the detection of heavy metal ions, which is also of great significance for ecological protection and environmental monitoring.